Making constitutions : presidents, parties, and institutional choice in Latin America - Negretto, Gabriel L. (Cambridge ; New York : Cambridge University Press, 2013)
'Negretto provides the first systematic explanation of the origins of constitutional designs from an analytical, historical and comparative perspective. Based on analysis of constitutional change in Latin America from 1900 to 2008 and four detailed case studies, Negretto shows the main determinants of constitutional choice are the past performance of constitutions in providing effective and legitimate instruments of government and the strategic interests of the actors who have influence over institutional selection. The book explains how governance problems shape the general guidelines for reform, while strategic calculations and power resources affect the selection of specific alternatives of design. It emphasizes the importance of events that trigger reform and the designers' level of electoral uncertainty for understanding the relative impact of short-term partisan interests on constitution writing. Negretto's study challenges predominant theories of institutional choice and paves the way for the development of a new research agenda on institutional change'--
Machine generated contents note: Part I. The Logic of Constitutional Choice: Theory and Data: 1. Constitutional change and patterns of design; 2. A two-level theory of constitutional choice; 3. Determinants of variation in constitutional choice; Part II. Case Studies: The Origins of Reforms: 4. Constitutional change as a means to consolidate power: Argentina 1949; 5. Constitutional change as a strategy to redistribute power: Argentina 1994; 6. Constitutional change as a response to state failure: Colombia 1991; 7. Constitutional change as a remedy for ungovernability: Ecuador 1998.
Includes bibliographical references (pages 263-277) and index.
Keywords: Representative government and representation -- Latin America -- History -- 20th century; Constitutional history -- Latin America -- History -- 20th century; POLITICAL SCIENCE / General; Latin America -- Politics and government -- 20th century